Therapy Brain Gym terhadap Short Memory Anak Retardasi Mental - Panzilion Panzilion; Juli Andri; Padila Padila (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of brain gym therapy on increasing short memory of school-age mentally retarded children. This type of research is a quantitative study with a quasi-experimental design, one groups pre and post test design. The results showed that the t-dependent value of the brain gym pre-post test, with a p-value of 0.000 and the mean value for children who were given brain gym intervention was 10.60 with a standard deviation of 0.996. In conclusion, there is an effect of brain gym therapy on increasing short memory of school-age children at State Elementary School 05 Bengkulu City. Keywords: Brain Gym, Mental Retardation, Short Memory, School Age